Dietary inflammatory index and risk of non-alcoholic fatty liver disease and advanced hepatic fibrosis in US adults - Zhang, Zhongmian; Wang, Lan; Lin, Zili; Yan, Weitian; Chen, Jiaqin; Zhang, Xiyan; Ye, Wangyu; Li, Jian; Li, Zhihong (Frontiers in Nutrition, 2023)
Background and aims This study aims to investigate whether the Dietary Inflammatory Index (DII) is associated with non-alcoholic fatty liver disease (NAFLD) and advanced hepatic fibrosis (AHF) among non-institutionalized adults in the United States. Methods Utilizing data from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2016, a total of 10,052 adults aged ≥18 years were included in the analysis. We used multivariable analysis, controlling for demographic variables, to evaluate the association between DII and NAFLD and AHF, a restricted cubic spline (RCS) was used to model the non-linear relationship between DII and NAFLD. Results For 10,052 participants, DII ranges from -4.63 to 5.47. Compared with quartile 1, higher DII group were associated with higher levels of female, separated/divorced, lower education level, heavy alcohol use, current smoke status, BMI, poverty income ratio, and waist circumference. DII also showed a significantly positive correlation with ALT, AST. In the fully adjusted multivariable model, DII was positively associated with the presence of NAFLD (OR 1.09, 1.06–1.13 CI, p trend <0.0001), and AHF (OR 1.15, 1.07–1.23 CI, p trend <0.001). The association remained statistically significant after stratified by gender in terms of NAFLD, but in case of AHF only in males (Q4 vs. Q1: OR 2.68, 1.63–4.41 CI, p trend <0.0001) was statistically significant. In the RCS models, the relation of DII and NAFLD started increase rapidly until around 1.80 and then started relatively flat afterward. Conclusion Higher pro-inflammatory level was associated with higher risk of NAFLD in males and females, and with higher risk of AHF in males but not in females. Therefore, strategies to promote an Zhang anti-inflammatory diet should be considered to prevent and ameliorate NAFLD and AHF in adults.